Personalidad y desempeño académico en la Universidad Francisco de Paula Santander, seccional Ocaña - Yuri Alfonso Carrascal-Gómez; Jorge de Jesús Cañizares-Arévalo; Henry Eliseo Navarro-Chinchilla (Mundo Fesc)
In Colombia, research related to academic performance is generally focused on the perspective of analyzing an individual's socio-emotional skills, without identifying and examining the causes that generate these behaviors that impact personality. Consequently, there is a need to fill a gap in the literature on the subject in Colombia, directing research on academic performance to more specific factors related to students' personality. In this sense, this research was proposed with the objective of establishing the relationship between personality and academic performance of students at the Francisco de Paula Santander University, Ocaña branch, for which a Five-Factor Model (FFM) personality test was applied to a sample of 173 students. The results show agreement with what has been established by the literature on the subject, the dimensions of Conscientiousness and Extraversion are reported as drivers of greater performance, while the Emotional Stability dimension generates negative marginal effects. However, these results are only explicitly present in the female sample, leading us to investigate whether there are cultural or simple design reasons that prevented the male responses from being significant, with the exception of the cognitive ability factor. Another relevant aspect to consider in consolidating a predictive model of academic performance is the negative effect of being a victim of armed conflict in a region historically affected by violence.